The Impact of Different Light-Reflecting Materials Compositions of (LaBr3:Ce) Scintillation Detector on Spent Nuclear Fuel Gamma Spectrum - El-Tayebany, R. A. (Atom Indonesia, 2024)
The Scintillation detectors are extensively employed in nuclear safeguards, nuclear security fields, radioactive material testing, and physics research. Light-reflecting materials of (LaBr3:Ce) scintillation detectors positively affect their ability to capture light. Our goal is to investigate the characteristics of various reflectors by MCNPX code. In this paper, high-activity fission products from the spent fuel, identified as the utilized radionuclides 152Eu, 154Eu, 134Cs, 137Cs, and 243Cm, have been used in the simulation. Also, short-lived fission products, and short-lived actinides (239U and 239Np), which have decay heat in the timeframe of severe accident analysis, have been included. The findings of this investigation are consistent with the discovery that LaBr3:Ce delivers superior resolution. Additionally, some closely spaced peaks in the spectra of numerous radioisotopes could be resolved by the LaBr3:Ce detector. With different energy lines, the spectral responses of the scintillators' various reflectors were evaluated.